2022
DOI: 10.3892/ijmm.2022.5157
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin enhances the L‑carnitine‑mediated preventive effects on skeletal muscle atrophy in cirrhotic rats by modulating the gut‑liver‑muscle axis

Abstract: The gut-liver-muscle axis is associated with the development of sarcopenia in liver cirrhosis. The present study aimed to illustrate the combined effects of rifaximin and L-carnitine on skeletal muscle atrophy in cirrhotic rats with steatohepatitis. For this purpose, a total of 344 Fischer rats were fed a choline-deficient L-amino acid-defined (CDAA) diet with the daily oral administration of rifaximin (100 mg/kg) and/or L-carnitine (200 mg/kg), and measurements of psoas muscle mass index and forelimb grip str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“… 6 On the other hand, no changes in physical SIP or muscle-related changes have been published in humans treated with rifaximin, although translational studies have alluded to them. 35 , 48 Also underlining the local impact of RiVM, the salivary microbiome was unaffected using 16SrRNA sequencing in patients with MHE without prior OHE. In contrast, in patients with MHE and prior OHE, prior studies have shown that microbiota changes with rifaximin are more marked, especially with metagenomics, but RiVM effects have not yet been studied in this population.…”
Section: Discussionmentioning
confidence: 99%
“… 6 On the other hand, no changes in physical SIP or muscle-related changes have been published in humans treated with rifaximin, although translational studies have alluded to them. 35 , 48 Also underlining the local impact of RiVM, the salivary microbiome was unaffected using 16SrRNA sequencing in patients with MHE without prior OHE. In contrast, in patients with MHE and prior OHE, prior studies have shown that microbiota changes with rifaximin are more marked, especially with metagenomics, but RiVM effects have not yet been studied in this population.…”
Section: Discussionmentioning
confidence: 99%
“…[ 47 ] It inhibits skeletal muscle atrophy in cirrhosis or steatohepatitis through the intestinal‐liver‐muscle axis. [ 48 ] l ‐Carnitine is a safe and helpful supplement to treat skeletal muscle sickness, cardiovascular disease, neurological disease, hepatobiliary disease, or pregnancy difficulties, according to several significant evidences.…”
Section: Discussionmentioning
confidence: 99%
“…(Murata et al, 2022) [53] Alzheimer's disease (AD) ALC Mitochondrial membrane potential decline and attenuation in Na+ K+ ATPase functionality, accompanied by reduced mfn1, mfn2, and BCL2 protein concentrations.…”
Section: Nutritional Profile Of L-carnitinementioning
confidence: 99%